Mapping commercial and business service occupations by comparing qualificational and factual requirements - Annen, Silvia [Verfasser]; Tiemann, Michael [Verfasser] (My University, 2015)
This contribution presents the results of a CATI-survey of 2,304 employees in commercial and business service occupations. It was conducted in the context of the BIBB project on "similarities and differences between commercial and business service occupations" to "gain deeper understanding on tasks, skills and self-images of service-workers as well as their demand for further qualification and their future prospects. The sample was stratified into 10 occupational groups. These groups were clustered according to how well their contents matched." (Text extract, BIBB-Doku)
Keywords: S 6.4.1 Kaufleute; L 1 Curricula & Lehrpläne; G 1.2.3 Qualifikationsentwicklungen; Kaufmännischer Beruf; Berufsgruppe; Ausbildungsinhalt; Qualifikationsprofil; Tätigkeitsmerkmal; Qualifikationsanforderung; BIBB-/BAuA-Erhebung